PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA LAKI-LAKI DAN PEREMPUAN MELALUI MODEL DISCOVERY LEARNING DI SEKOLAH DASAR - Nursaidah; Nisa Khoerunajah; Irwan Maulana; Ina Setiawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine differences in mathematical problem-solving skills in cube material between male and female students after applying the Discovery Learning model in Grade IV SDN 4 Awirarangan, Kuningan Regency. This quantitative study used a One Group Pretest-Posttest Design. The research subjects were all 21 Grade IV students, consisting of 12 male and 9 female students. The research instrument used was a problem-solving test based on Polya's stages: understanding the problem, devising a plan, carrying out the plan, and looking back. The data analyzed were posttest scores grouped by gender. Data analysis included the Shapiro-Wilk normality test, Levene's homogeneity test, and hypothesis testing using the Independent Sample t-Test or Mann-Whitney U Test at significance level α = 0.05. The results showed that there is a significant difference in mathematical problem-solving ability between male and female students, with t = 6.664 and significance < 0.001. The mean posttest score of female students (85.55) was significantly higher than that of male students (46.66). Therefore, it can be concluded that the implementation of the Discovery Learning model produced a significant difference in mathematical problem-solving ability in cube material between male and female students in Grade IV SDN 4 Awirarangan, Kuningan Regency.